Diversity Of Thought and Economic Identity in Contemporary Society: Philosophical Perspectives - Khoshimov Hakimjon Abduqaxxor ugli (International Scientific and Current Research Conferences, 2025)
This article investigates the intersection of intellectual pluralism (diversity of thought) and economic identity in modern societies from a philosophical vantage point. It explores how individuals and communities define themselves economically (as workers, consumers, entrepreneurs, marginalized classes, etc.) and how varied worldviews influence, challenge, or reinforce those identities. Through a critical review of philosophical, sociological, and economic literature, the study frames economic identity not as a rigid category but as a dynamic and contested domain shaped by ideological, cultural, and power-laden discourses.